From These Honored Dead : Historical Archaeology of the American Civil War - Babits, Lawrence Edward; Scott, Douglas D.; Geier, Clarence R. (Book collections on Project MUSE., 2014)
This book contains sixteen original essays that highlight the role of historical archaeology in our understanding of the American Civil War.